Optimalisasi Kinerja Guru melalui Budaya Organisasi Dinamis dan Gaya Kepemimpinan Transformasional di SMPN 36 Sijunjung - Nova Liza; Suswati Hendriani (Departement of Mathematics Education, 2024)
This research aims to optimize teacher performance at SMPN 36 Sijunjung through the application of a dynamic organizational culture and transformational leadership style. The research method used is a qualitative case study approach with data collection techniques through observation, interviews, document analysis and triangulation to ensure the validity of the data. The research results show that a dynamic organizational culture, which encourages innovation, collaboration and open communication, can increase teacher motivation and involvement in carrying out their duties. Apart from that, the transformational leadership implemented by the school principal, which involves inspiration, collaboration, motivation, knowledge updates and teacher empowerment, has a positive effect on improving teacher performance. Thus, the combination of dynamic organizational culture and transformational leadership has proven effective in optimizing teacher performance at SMPN 36 Sijunjung. This research provides an important contribution to the development of school management strategies in improving the quality of education.